Evaluation of one-stop diagnosis and management at the collaborative national standardized metabolic disease management center - Yin, Huihui; Yu, Shanshan; Li, Han; Shi, Chunhong; Wang, Weiping; Men, Lili; Jia, Lihong (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the effectiveness of diagnosis and treatment at the collaborative National Standardized Metabolic Disease Management Center.MethodsA nationally standardized selection process was used to recruit the healthcare team, followed by standardized training and assessment. The management center was equipped with coordinated healthcare resources, and clear workflows and responsibilities were established. A quality control management model was implemented throughout all stages. A convenience sample of 452 patients treated at the center between January 2018 and July 2023 was selected. After one year of management, a self-comparison was conducted to evaluate the impact of one-stop diagnosis and management on patients’ weight, fasting blood glucose, glycated hemoglobin, blood pressure, blood lipids, diet, and exercise.ResultsAfter one year of management, patients showed significant reductions in weight, BMI, waist circumference, and visceral fat compared to baseline data (P=0.000). Fasting blood glucose and glycated hemoglobin levels decreased significantly (P<0.0001), as did systolic and diastolic blood pressure (P<0.05). Triglycerides, low-density lipoprotein cholesterol, and total cholesterol levels also decreased significantly (P<0.05), but high-density lipoprotein levels did not change significantly (P=0.5298). Improvements were observed in dietary and exercise behaviors (P<0.05), though no significant change was observed in salt intake (P=0.648).ConclusionThe collaborative model at the National Standardized Metabolic Disease Management Center enhances comprehensive patient management. Combined with lifestyle guidance on diet and exercise, the model improves the prevention and control of glycemic and lipid metabolism indicators in diabetes patients.